The Influence of Tone at the Top and Knowledge Sharing on Risk Culture Mediated by Cooperation : (Case Study of Civil Servants at the Madiun City Inspectorate) (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of tone at the top and knowledge sharing on risk culture, with collaborative working as a mediating variable among civil servants (ASN) at the Madiun City Inspectorate. The study used a descriptive quantitative approach, using primary survey data analyzed using SmartPLS 4. This study tested seven hypotheses regarding the relationships between the variables.The results showed that five hypotheses were accepted and two hypotheses were rejected. Tone at the top, knowledge sharing, and collaborative working had a positive effect on risk culture. Knowledge sharing also had a positive effect on collaborative working and risk culture through collaborative working. However, tone at the top had no effect on collaborative working and no effect on risk culture through the mediating variable. Theoretically, these results indicate that tone at the top is not always able to improve risk culture through collaborative working. Practically, this study emphasizes the importance of leadership in building a risk culture through active involvement in planning, measuring, reporting, and evaluating performance at the Madiun City Inspectorate.